Fermentative microbiota and chemical characterization of traditional date vinegar with promising biotechnological applications - Al-Malki, Fatma A.; Al-Kharousi, Zahra S.; Guizani, Nejib; Al-Bulushi, Ismail M.; Al-Sadi, Abdullah M. (Frontiers in Sustainable Food Systems, 2023)
Introduction The indigenous microbiota of traditional date vinegar is inadequately reported in the literature, yet its understanding is necessary for the industrial development of this product. This study aimed to perform microbiological and chemical analyses of traditional date vinegar. Methods Forty home-made samples (HMS) and laboratory-made samples (LMS) of date vinegar were analyzed. Escherichia coli, coliforms, and Enterobacteriaceae were enumerated using conventional plate methods to evaluate the hygienic quality. Bacteria and yeasts were identified by polymerase chain reaction. Acetic acid, ethanol, and methanol contents were analyzed by headspace gas chromatography. Results and Discussion Escherichia coli was not detected in any sample. Coliforms and Enterobacteriaceae occurred in 75 and 67% of HMS, respectively, and in 3.6% (both groups) of LMS. The LMS had better hygienic quality and supported better growth of yeasts and AAB than the HMS. Thirty-five yeasts belonged to 6 genera and 55 acetic acid bacteria (AAB) to 5 Gluconobacter species. The highest content of ethanol correlated with the presence of Saccharomyces cerevisiae. Gluconobacter japonicus and Gluconobacter oxydans tolerated 7.5% ethanol. Gluconobacter frateurii survived at pH 2.59. The percentage of acetic acid was less than the international recommended standard levels and ranged from 0.09% to 3.38%, and 0.03% to 3.46% in HMS, and LMS, respectively. The content of ethanol ranged from 0.14% to 2.17%, and 0.07% to 7.81% in HMS, and LMS, respectively. Methanol was less in LMS (≤ 0.06%) than in HMS (≤ 0.17%). Utilizing the traditional method for producing date vinegar does not assure the production of true and safe vinegar that contains the specified levels of acetic acid and ethanol. It may also contain unacceptable levels of the toxic chemical methanol. However, a high microbial diversity of yeasts and Gluconobacter spp. was identified which indicates the potential of producing a high-quality and safe product by modifying the production process possibly by using the isolated yeasts and AAB as starter cultures.